1998
DOI: 10.1128/jvi.72.10.8052-8060.1998
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Lethal Encephalomyocarditis Virus Infection in the Absence of Serum-Neutralizing Antibodies

Abstract: Although the ability of serum-neutralizing antibodies to protect against picornavirus infection is well established, the contribution of cell-mediated immunity to protection is uncertain. Using major histocompatibility complex class II-deficient (RHAβ−/−) mice, which are unable to mediate CD4+ T-lymphocyte-dependent humoral responses, we demonstrated antibody-independent protection against lethal encephalomyocarditis virus (EMCV) infection in the natural host. The majority of RHAβ−/− mice inoculated with 104 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Levels of lymphocyte activation, notably of both CD4 ϩ and CD8 ϩ T cells, were also impaired in CD1d-KO EMCV-infected mice compared to those in wild-type animals. Consistent with the observations made in the present study, it was reported previously that in vivo resistance to EMCV infection is dependent on both CD4 ϩ and CD8 ϩ T cells (43,44).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Levels of lymphocyte activation, notably of both CD4 ϩ and CD8 ϩ T cells, were also impaired in CD1d-KO EMCV-infected mice compared to those in wild-type animals. Consistent with the observations made in the present study, it was reported previously that in vivo resistance to EMCV infection is dependent on both CD4 ϩ and CD8 ϩ T cells (43,44).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, it is plausible that CD1d-restricted T cells and/or CD1d-expressing APC serve as important mediators of antiviral T-cell responses, especially after the rapid initial productive viral infection round. Furthermore, their role may be essential for the eventual suppression of viral replication, since T-cellmediated responses were previously shown to confer protection against EMCV infection in vivo (43,44). The differences between wild-type and CD1d-KO mouse resistance are greatest at early-to-intermediate stages of the infectious cycle, consistent with rapid innate immune-like effects attributed to the CD1d system.…”
Section: Discussionmentioning
confidence: 77%
“…Splenocytes (1 × 10 6 per well in 24‐well plates) were infected with EMCV‐D (multiplicity of Infection 0·1/cell to ensure viable cells for cytokine production) as previously described 50–54 or treated with 1 μg/ml anti‐CD3 monoclonal antibody (145‐2C11) bound to 24‐well plates. Murine IL‐12 was added where indicated at 1 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The virus infects pancreatic islet cells, the nervous system, and heart muscle in vivo but clearance of the virus results in the resolution of acute disease 44–49 . T lymphocytes, macrophages, NK cells, and NK‐like spleen cells have been reported to contribute to EMCV‐D resistance, and wild‐type (WT) mice can be protected by IL‐12 treatment and consequent IFN‐γ production 47–51 . Resistance to EMCV‐D correlates with early IFN‐γ production and IFN‐γ‐receptor‐deficient mice are highly susceptible, even when treated with IL‐12 51–54 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are several picornaviruses for which human seropositivity is low and infection typically is asymptomatic. Some of these viruses also can be highly antigenic and induce potent humoral and cellular immune responses to mediate indirect killing of tumor cells ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%